Judith 5:5-21 ou le récit d’Akhior: les mémoires dans la construction de l’identité narrative du peuple d’Israël - Gil, Roger (Vetus Testamentum, 2014)
In the book of Judith, the Ammonite official Achior tries to dissuade Holofernes from engaging in war against the people of Israel. In fact, he is convinced that the God of Israel will protect his people. Achior’s description of these “mountain folk” is an example of how the identity of an entire people can be conceived. Like a single person’s identity, collective identity finds its roots in memory and, by consequence, within the various human memory systems. In particular, one can distinguish an episodic (“remembering” events or situations already experienced) and and a semantic (“knowing” about events, concepts, objects, ideas or facts) memory.